Identification of contaminating mollicutes in mammalian cell culture as spiroplasma species. (June 2021) - Windsor, Helena; English, Christie
Abstract: Cell cultures have provided an ideal habitat for a wide variety of Mycoplasma and Acholeplasma species since the earliest days of in-vitro culture. The possibility of contamination with Spiroplasma species was addressed by Regulatory Authorities due to the increased commercial use of insect cells, recognising that Spiroplasmas have been isolated from many types of arthropod and also that insect cell cultures support Spiroplasma growth as they have been used for cultivation of fastidious species. In this study we re-examined two cell culture samples previously confirmed as contaminated with mollicutes by cultural methods. One isolate had undergone sequencing which had placed it in the S. citri phylogenetic group, whilst the other had not been identified. Using modern sequencing methods we were able to further identify both isolates to species level.